USE OF THE INTERNATIONAL EXPERIENCE OF ANTI-CRISIS MANAGEMENT OF ENTERPRISES IN THE REPUBLIC OF KAZAKHSTAN - Kairbekuly Aydin; Ostapenko Irina Ivanovna; Ostapenko Elena Ivanovna; Kenzhebaeva Zhanat Elubaevna (Academic Journal of Physical and Chemical Sciences, 2020)
The theoretical and practical aspects of the formation of professional anti-crisis management of enterprises in the Republic of Kazakhstan and the use of international experience in cooperation of state bodies with self-regulating organizations in the field of bankruptcy are considered in the article. Existing discrepancies call for a new and adequate theoretical and conceptual foundations of anti-crisis state economic regulation and implementation of applied mechanisms of promoting the economic growth and increasing the base of growth through stimulating the direction of financial flows to development of domestic commodity production by means of taxation and regulation of the financial services sector, implementing the concept of import substitution by creating additional demand for domestic products, including through public procurement and implementation of mechanisms of attracting capital from temporary financial instability areas.